Análise dos atendimentos a vítimas de acidente de transporte terrestre realizados em um hospital público de grande porte - Thaís Moreira Oliveira (2019)
Trauma is one of the top ten causes of death in the world. Among the types of trauma, land transport accidents (LTA) impact illness patterns and mortality, mostly of young victims. Trauma is an acute and potentially serious injury, thus demands immediate care and of high complexity. Knowledge about the outcomes of services rendered in emergency care until hospital discharge can contribute to the reassessment of patient turnout and quality of care delivered, which in turn increases resolubility and improvement of healthcare services. The objective of this study was to analyze the care provided to victims of land transport accidents in a large public hospital. This study is a cross-sectional study which analyzed 431 adult LTA victims who underwent risk classification (RC) and hospitalized in 2016. Sociodemographic variables related to accident, emergency room care and hospital outcome were analyzed considering two groups: 'PS': hospitalized in emergency room and 'IU': admitted in hospital. Also, descriptive analysis of the variables was done. The variables of the 'PS' and 'UI' group were compared using the Mann-Whitney test for continuous variables. Differences between proportions were tested by Pearson's Chi-square test and Fisher's exact test. P values <0.05 were considered significant. The subjects were predominantly male (81.9%), lived without a partner (80.0%) and between 20 and 40 years (66.6%). Major trauma accounted for 56.9% of RC in the UI group while falls (66.7%) was the most frequent for the 'PS' group (p = 0.0022). Also, the most common clinical priority level was orange/very urgent (78.4%). The median time between registering, RC and duration of RC was 2.88 minutes (IQ = 1.63-5.32), 1.32 minutes (IQ = 1.02-1.77), respectively. Motorcycle accidents (68.5%) followed by road accidents (13.2%) were the most common reasons for the use of urgent care units Regarding type of injury, the 'no apparent injury' category was more frequent in the 'PS' group (56.7%) (p-value = 0.0032). In the 'UI' group, open fractures (86.7%) (p-value <0.001) and long bone fractures (100.0%) (p-value <0.0001) prevailed. The most affected body regions were the upper limbs in the 'PS' group (53.9%) (p-value <0.001) and lower limb (64.3%) in the 'UI' group (p-value = 0.004). The median duration of hospital stay was 1.38 (IQ = 0.86-2.36) days for the 'PS' group and 7.15 (IQ = 3.5-12.86) days for the 'UI' group. Majority (89.8%) of the patients were discharged. The analysis of the healthcare services provided by the institution indicates its role in offering emergency care services to LTA victims. The immediate assistance offered in a timely manner contributed to meeting the needs of the user in an acute situation; moreover the therapy provided by the hospital may have contributed to the survival of these patients